The interplay of personal storytelling with rational justifications in online discussions: A qualitative exploration of news user comments - Jakob, Julia (Javnost-The Public, 2022)
In light of theoretical controversies among deliberation scholars, this study thoroughly explores the interplay of personal storytelling with rational justifications in online discussions. In a qualitative content analysis, it examines how this relationship manifests in online news user comments on the public role of religion and secularism in society from the period of August 2015 until July 2016. To provide more general interpretive insights, the study analyses highly comparable data from multiple countries. The material stems from the websites of nine daily news media in Australia, the United States, Germany and Switzerland. In the investigated online news user comments, personal storytelling regularly interplays with rational justifications in the shape of a narrative rationality and a supportive narrativity. While narrative rationality relies on personal narratives to make a point in the form of a rational justification, supportive narrativity builds on personal experiences referenced in passing to further reinforce a general line of reasoning. Personal storytelling thus plays a vital role in justifying the normative rightness of the positions that the commenters take on the contested issue. This supports normative theories that acknowledge the merit of personal storytelling for public deliberation and provides new impulses for their specification.